The Influence of Perceived Ease of Use and Perceived Risk on Continuance Intention to Use with E-Satisfaction as an Intervening Variable (Study on Gojek Users in Malang City) - Enjelika; Sudarmiatin; Pratikto, Heri (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to investigate the effects of perceived risk and perceived ease of use on the continuance intention to use Gojek online transportation in Malang City, with e-satisfaction serving as a mediating variable. Using a quantitative method using SEM-PLS analysis and a survey with 385 respondents. The findings indicate that e-satisfaction has a positive and substantial impact on continuing intention to use, while perceived ease of use has a positive and significant impact on e-satisfaction. Perceived risk, however, has no discernible impact on e-satisfaction or intention to continue use. According to mediation testing, e-satisfaction mediates the correlation between perceived ease of use and continuance intention to use, but it does not mediate the correlation between perceived risk and continuance intention to use. This result demonstrates how crucial e-satisfaction is in promoting the continuance intention to use online transportation services.